POTENSI SEKTOR EKONOMI DALAM MENINGKATKAN PERTUMBUHAN EKONOMI REGIONAL DI KABUPATEN MIMIKA - Sandy Mart Prays Kawab; Herul Syam; Abu Bakar (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to identify potential economic sectors that can increase economic growth in Mimika Regency. The data used came from the Central Bureau of Statistics of Mimika Regency with data collection techniques through observation and documentation. The analysis used includes (LQ), (SS), (TK), (MRP), Overlay, and (DLQ). The results found in this study are the growth rate in Mimika Regency totaling 16 sectors that are leading sectors, including the Construction sector, Wholesale and Retail Trade; Repair of Cars and Motorcycles, Transportation and Warehousing, Provision of Accommodation and Drinking Food, Real Estate, Corporate Services, and the growth rate of GRDP in the 2019-2023 period in Mimika Regency without the Mining and Quarrying sector states that the Agriculture, Forestry and Fisheries, Construction, Government Administration, Defense and Compulsory Social Security sectors in Mimika Regency have great potential, which will directly improve the welfare of the community and can have a positive impact on the community.